2018
DOI: 10.1021/acs.nanolett.8b01170
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Single-Photon Emission from Carbon-Nanotube Dopant States Coupled to Silicon Microcavities

Abstract: Single-walled carbon nanotubes are a promising material as quantum light sources at room temperature and as nanoscale light sources for integrated photonic circuits on silicon. Here, we show that the integration of dopant states in carbon nanotubes and silicon microcavities can provide bright and high-purity single-photon emitters on a silicon photonics platform at room temperature. We perform photoluminescence spectroscopy and observe the enhancement of emission from the dopant states by a factor of ∼50, and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 40 publications
0
44
0
Order By: Relevance
“…[160] Coupling between 2D photonic crystal microcavities and (6,5) SWCNT sp 3 defect state emission has also been used to fabricate high purity SPE with emission enhancement by a factor of ≈50 and emission rates as high as ≈1.7 × 10 7 Hz. [161] Although the scalability of most defect-based SWCNT SPE systems remains largely unexplored, it has been found that sp 3 defects sites in ultrashort nanotubes (≈40 nm length) dramatically increase their photoluminescence, suggesting their potential in highly scaled photonic systems. [7] One of the shortcomings of the sp 3 defect system is the spectral broadening caused by the diversity of emitting states created through functionalization.…”
Section: Swcnt Single-photon Emittersmentioning
confidence: 99%
“…[160] Coupling between 2D photonic crystal microcavities and (6,5) SWCNT sp 3 defect state emission has also been used to fabricate high purity SPE with emission enhancement by a factor of ≈50 and emission rates as high as ≈1.7 × 10 7 Hz. [161] Although the scalability of most defect-based SWCNT SPE systems remains largely unexplored, it has been found that sp 3 defects sites in ultrashort nanotubes (≈40 nm length) dramatically increase their photoluminescence, suggesting their potential in highly scaled photonic systems. [7] One of the shortcomings of the sp 3 defect system is the spectral broadening caused by the diversity of emitting states created through functionalization.…”
Section: Swcnt Single-photon Emittersmentioning
confidence: 99%
“…This has been recently performed by coupling a nanotube with aryl sp 3 defects as emitting sites and individualized in sodium deoxycholate with a silicon photonic crystal microcavity. [66] Coupling the single photon source to the mode of the silicon microcavity leads to an emission rate enhancement of two orders of magnitude (1.7x10 7 photons per second). [66] These recent results represent a breakthrough as hybrid nanotubes can be used as high emission, room temperature stable single photon sources which can be tuned when coupled to the mode of an optical cavity.…”
Section: Hybrid Nanotubes For Cavity Quantum Electrodynamicsmentioning
confidence: 99%
“…[66] Coupling the single photon source to the mode of the silicon microcavity leads to an emission rate enhancement of two orders of magnitude (1.7x10 7 photons per second). [66] These recent results represent a breakthrough as hybrid nanotubes can be used as high emission, room temperature stable single photon sources which can be tuned when coupled to the mode of an optical cavity. This opens up new possibilities for quantum optics and cryptography.…”
Section: Hybrid Nanotubes For Cavity Quantum Electrodynamicsmentioning
confidence: 99%
“…On-demand single photons are one of the key elements required for optical quantum information processing. [1][2][3][4][5] Among many candidates for the generation of single photons, [6][7][8][9][10][11][12] semiconductor quantum dots (QDs) are promising for their high stability, good repetition rate, and compatibility with quantum photonic networks. 13,14 Notably, III-nitride QDs 15 offer a variety of attractive properties, such as large exciton binding energies and large band offsets, which allow high-temperature operation.…”
Section: Introductionmentioning
confidence: 99%